THE MODULATION OF DRUG EFFLUX TRANSPORTER BY CURCUMIN IN MCF7 BREAST CANCER CELLS AFTER REPEATED EXPOSURE OF ENDOXIFEN AND ESTRADIOL - Hertanto, Robby; Bastian, Wilson; ., Paramita; Louisa, Melva (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of the present study was to determine whether curcumin (CM) can prevent drug sensitivity of breast cancer (BC) cells when E and Î²-E2 are administered together and whether the underlying mechanism involves modulation of drug efflux transporters. Methods: MCF7 BC cells were treated with the vehicle only, E+Î²-E2, or E+Î²-E2+CM repeatedly for 8 weeks. Afterward, the cells were harvested, counted, and isolated for total RNA extraction. Total RNA was then processed into cDNA and further processed for the determination of mRNA expression patterns of drug efflux transporters (P-glycoprotein, BCRP, and MRP1). Results: Decreased sensitivity of BC cells was shown by the increased cell viability of MCF7 cells after 8 weeks. This condition was accompanied with increased mRNA expression of P-glycoprotein, BCRP, and MRP1 in cells treated with E+Î²-E2, as compared with the vehicle only. CM, administered in combination with E+Î²-E2, resulted in decreased cell viability versus E and Î²-E2 and also decreased in mRNA expression of P-glycoprotein, BCRP, and MRP1. Conclusion: CM partially reversed the sensitivity loss of BC cells to E in the presence of Î²-E2 by modulating drug efflux transporters.